Resistência antimicrobiana, genotipagem capsular e deteção de genes de resistência de Streptococcus pneumoniae isolados de crianças não vacinadas usuárias de creches em Fortaleza - Laranjeira, Bruno Jaegger (2014)
Streptococcus ( S. ) pneumoniae is considered the principal causative agent of mor bidity and mortality in children younger than five years of ag e. All pneumococcal diseases are initiated by establishing a S. pneumoniae colonization in nasopharynx. The main risk factor for colonization is crowding, as in children attending day care. During the last decades, the increasing amount of resistant S. pneumoniae strains to β -lactams and other classes of antimicrobials has modified the treatment of pneumo coccal infection. At present, nearly 13 serotypes respond for more than 85% of invasive iso lates. The 10-valent pneumococcal polysaccharide-conjugated vaccine (PCV-10) has rece ntly been included in the national vaccination schedule. The aims of this study were t o determine the prevalence, antimicrobial resistance and genotypes of S. pneumoniae isolated of carriage children attending day care centers in Fortaleza, Brazil, as well as to assess the potential coverage of the PCV-10. Between January and December of 2011, isolates from carrier children were recovered by nasopharyngeal swabs. Susceptibility to penicillin, amoxicillin, erythromycin, sulfamethoxazole-trimethoprim, clindamycin, were de termined by e-test method. Detection of penicillin resistance genes was performed by PCR as say. Capsular genotyping of carriage isolates was performed by multiplex PCR assay. S. pneumoniae were isolated in 165 (87.3 %) of 291 samples of children attending day care cente rs. Of the 162 isolates from carriage was found a resistance rate of 27.8% for penicillin, 75 .3% to trimethoprim / sulfamethoxazole, 13.6% to erythromycin and 10.5% to clindamycin. No resistance was detected to ceftriaxone and amoxicillin. The percentage of S. pneumoniae isolates at least one mutation in the penicillin resistance genes was 68.2%. Capsular Gen otypes was indentified in 115 isolates, of 129 tested. Genotypes most common were 6A/6B, 14, 1 5B/15C, 19F and 23F, with serotypes 6A/6B, 14, 19F and 23F more associated with resista nce. The estimated coverage for VPC-10 was 74.4%. This study showed that the rate of S. pneumoniae carriers is high, as well as resistance to antibiotics penicillin and sulfametho xazole / trimethoprim, and the potential cover of VPC-10 is raised against S. pneumoniae genotypes identified isolated from children attending day care centers in Fortaleza.